Ovarian Cancer Screening and Mortality in the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS): A Randomized Controlled Trial. Issue 6 (June 2016) - Jacobs, Ian J.; Menon, Usha; Ryan, Andy; Gentry-Maharaj, Aleksandra; Burnell, Matthew; Kalsi, Jatinderpal K.; Amso, Nazar N.; Apostolidou, Sophia; Benjamin, Elizabeth; Cruickshank, Derek; Crump, Danielle N.; Davies, Susan K.; et al.
Abstract : (Abstracted from Lancet 2016;387:945–956) Ovarian cancer (OC) is diagnosed in most women at an advanced disease stage when prognosis is poor and 5-year survival is low. With the hope that death rates from OC can be reduced through early detection, there has been an intense effort to identify predictors of OC that can be used as markers to screen the general population.